Sosialisasi Penerapan Konsep Manajemen Ritel Modern Dalam Usaha Kecil Menengah di Lingkungan Sekolah - Widiyarto, Sigit; Dellia Mila Vernia; N. Yeffa Afnita Apriliyani; Tony Margiyanto; Anjah Akhmad Ulinnuh (LPPM UMRI, 2025)
This research is motivated by the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in school environments in managing their businesses in the era of globalization. Many MSMEs lack understanding of modern retail management concepts, particularly in operational and financial management. The aim of this activity was to socialize the application of modern retail management concepts to 10 teachers at the Citra Binar Rahma Foundation through participatory and needs-based training. Training results show good understanding of basic retail management concepts and product/customer service strategies. However, challenges remain in understanding operational and financial management. The use of digital technology was enthusiastically received, but its implementation requires further support. It is recommended that further training focus on operational and financial management, along with technical support for the implementation of digital technology. Continuous evaluation is needed to ensure the sustainability of the training's impact